2024
DOI: 10.7150/thno.92909
|View full text |Cite
|
Sign up to set email alerts
|

G protein subunit alpha i2's pivotal role in angiogenesis

Chao-wen Bai,
Lu Lu,
Jia-nan Zhang
et al.

Abstract: Here we explored the potential role of Gαi2 (G protein subunit alpha i2) in endothelial cell function and angiogenesis. Methods: Genetic methodologies such as shRNA, CRISPR/Cas9, dominant negative mutation, and overexpression were utilized to modify Gαi2 expression or regulate its function. Their effects on endothelial cell functions were assessed in vitro . In vivo , the endothelial-specific Gαi2 shRNA adeno-associated virus (AAV) was utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…However, the downstream mediators of angiogenesis remain largely unknown. Bai et al 60 analysed the scRNA-seq data from STZ-induced diabetic mice and mice with OIR, and found that G protein subunit alpha i2 (Gαi2) was ubiquitously expressed across all cell types but significantly elevated in ECs, suggesting its potential role in ECs. Subsequent experiments validated the role of Gαi2 in activating the transcription factor NFAT to promote retinal pathological angiogenesis in DR mice (Figure 2).…”
Section: Pbmcmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the downstream mediators of angiogenesis remain largely unknown. Bai et al 60 analysed the scRNA-seq data from STZ-induced diabetic mice and mice with OIR, and found that G protein subunit alpha i2 (Gαi2) was ubiquitously expressed across all cell types but significantly elevated in ECs, suggesting its potential role in ECs. Subsequent experiments validated the role of Gαi2 in activating the transcription factor NFAT to promote retinal pathological angiogenesis in DR mice (Figure 2).…”
Section: Pbmcmentioning
confidence: 99%
“…As shown in Table 1 , the application of scRNA‐seq to the study of DR has seen significant advancements. 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 …”
Section: Introductionmentioning
confidence: 99%